ENHANCED GROWTH RESPONSE OF POTATO PLANT (SOLANUM TUBEROSUM L.) CV. GIGANT TO SLOW-RELEAS E FERTILIZERS - Pérez, Luis Carlos Mendoza; Gonzalez, Dr. Carlos Hernandez (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
The advent of the nineteenth century brought about a shift in agricultural practices in Mexico, marked by the introduction of inorganic fertilizers alongside traditional methods like organic residues and green manures. This transition was catalyzed by the realization that relying solely on organic matter led to yields below 1.5 Mg ha-1. The turning point arrived in the 1950s with the onset of the Green Revolution, characterized by the adoption of improved seeds and a surge in the use of agrochemicals and inorganic fertilizers. This shift resulted in a remarkable doubling of the national average yield (Núñez, 2001). While the increased application of nitrogen-based fertilizers significantly bolstered crop production, it also gave rise to a pressing issue: pollution. Specifically, nitrate leaching into subterranean aquifers emerged as a critical concern. This phenomenon led to the elevation of nitrate levels, with averages reaching 37 mg L-1 in the agriculturally significant Comarca Lagunera region (Castellanos and Peña-Cabriales, 1990). In other key potato-growing areas of Coahuila and Nuevo León, nitrate levels surged to 50 mg L-1 (Covarrubias and Contreras, 1997). Additionally, the state of Guanajuato recorded levels of 14.4 mg L-1 (Castellanos et al., 2001). These trends spotlight the crucial need for sustainable and ecologically responsible fertilizer practices in contemporary agriculture